Promoting fractional frequency reuse performance for combating pilot contamination in massive multiple input multiple output - Hany A. Atallah; Saad Almutairi; Adel Bedair Abdel-Rahman; Mohamed Elwekeil (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Massive multiple-input multiple-output (MIMO) improves spectrum efficiency by increasing the capacity of the wireless structure. Therefore, massive MIMO is promising for fifth generation (5G) wireless communications. In massive MIMO, channel estimation is a crucial part that should achieve reliable performance. Pilots are sent from the end-users to be used for estimating the channel. However, the problem of interference in pilot contamination affects the performance for cell-edge users. Specifically, pilot contamination appears when the same pilot sequence is utilized at the same time by more than one terminal. This lead to an inaccurate estimation of the channel. Consequently, the decoded data will not be reliable. For mitigating these pilot contamination effects, an enhanced fractional frequency reuse (eFFR) scheme is proposed that uses an algorithm in the allocation of pilot sequences to end users’ devices based on the locations of the users from the target base station (BS). The simulation results exhibit that the proposed scenario outweighs the traditional FFR within both signal to interference, and noise ratio (SINR), and capacity. Consequently, the suggested scenario enhances the performance of more than 80% of the cell terminals and the other 20% of the terminals have a slightly lower performance compared to the FFR.